Fresh biomass production and partitioning of aboveground growth in the three botanical varieties of Cynara cardunculus L. - Cravero, Vanina Pamela (2012)
Fourteen accessions of Cynara cardunculus were compared with the aim to evaluate the fresh biomass production and its partition, aiming at its potential use for industrial purposes. At anthesis stage, when plants have the maximum vegetative development, stalks, leaves and capitula were weighed separately. The percentage of dry matter per gram of fresh biomass was also calculated. The first capitulum components of each plant: bracts, flowers and remnant receptacle were also weighed separately. The total fresh biomass ranged between 1188 and 3235 g/plant, with variable values within each botanical variety, whereas the partition of the aboveground biomass was strongly affected by botanical variety. In both cardoons varieties, the percentage of dry matter ranged between 30 ? 35 % for all components of aboveground biomass, whereas in globe artichoke values ranged between 20 % for capitula and 40 % for leaves. Regarding capitula components, receptacle weight was of greatest importance in globe artichoke and cultivated cardoon. In wild cardoon flowers weight was more important than the other components. Results suggest that C. cardunculus var. scolymus and C. Cardundulus var. cardunculus, might be considered as double purpose crops if after the capitula (in globe artichoke) or leaves (in cardoon) harvest, the fresh matter remaining is artificially dry and cut. On the other hand, C. cardunculus var. sylvestris, might be incorporated into the culture system as an industry or energy crop due the low inputs management that it requires, its adaptability to the local conditions and its abovegroundbiomass production.